SCRAPPER Regulates the Thresholds of Long-Term Potentiation/Depression, the Bidirectional Synaptic Plasticity in Hippocampal CA3-CA1 Synapses - Hiroshi Takagi; Mitsutoshi Setou; Seiji Ito; Ikuko Yao (Neural Plasticity)
SCRAPPER, which is an F-box protein encoded by FBXL20, regulates the frequency of the miniature excitatory synaptic current through the ubiquitination of Rab3-interacting molecule 1. Here, we recorded the induction of long-term potentiation/depression (LTP/LTD) in CA3-CA1 synapses in E3 ubiquitin ligase SCRAPPER-deficient hippocampal slices. Compared to wild-type mice, Scrapper-knockout mice exhibited LTDs with smaller magnitudes after induction with low-frequency stimulation and LTPs with larger magnitudes after induction with tetanus stimulation. These findings suggest that SCRAPPER regulates the threshold of bidirectional synaptic plasticity and, therefore, metaplasticity.